Four : a Divergent Collection - Roth, Veronica (New York, NY : Katherine Tegen Books, an imprint of HarperCollins Publishers, 2014)
A collection of four pre-Divergent stories plus three additional scenes from Divergent, all told from Tobias's point of view, that follow Tobias's transfer from Abnegation to Dauntless, his Dauntless initiation, the first clues that a foul plan is brewing in the leadership of two factions, and the weeks after he meets Tris Prior.
The transfer --
Keywords: Science fiction; Social classes -- Fiction; Courage -- Fiction; Identity (Philosophical concept) -- Fiction; Dystopias. -- Fiction; Science fiction; Social classes -- Fiction; Courage -- Fiction; Identity -- Fiction; Courage; Dystopias; Identity (Philosophical concept); Science fiction; Social classes; Young adult fiction; Fiction